Multisensory Audiovisual Processing in Children With a Sensory Processing Disorder (I): Behavioral and Electrophysiological Indices Under Speeded Response Conditions - Molholm, Sophie; Murphy, Jeremy W.; Bates, Juliana; Ridgway, Elizabeth M.; Foxe, John J. (Frontiers in Integrative Neuroscience, 2020)
Maladaptive reactivity to sensory inputs is commonly observed in neurodevelopmental disorders. Little is known, however, about the underlying neural mechanisms. For some children, atypical sensory reactivity is the primary complaint, despite absence of another identifiable neurodevelopmental diagnosis. Studying Sensory Processing Disorder (SPD) may provide a window into the neuropathology of these symptoms. It has been proposed that a deficit in sensory integration underlies the SPD phenotype, but objective quantification is lacking. Here we used neural and behavioral measures of multisensory integration to test whether failure to integrate across the senses is associated with atypical sensory reactivity in SPD. An autism group served to determine if observed differences were unique to SPD. We tested whether children aged 6-16 years with SPD (N=14) integrate multisensory inputs differently from age-matched typically-developing controls (TD: N=54), or from children with an autism spectrum disorder (ASD: N=44). Participants performed a simple reaction-time task to the occurrence of auditory, visual, and audiovisual stimuli presented in random order, while high-density recordings of electrical brain activity were made. Children with SPD showed large reductions in the extent to which they benefited from multisensory inputs compared to TDs. The ASD group showed similarly reduced response speeding to multisensory relative to unisensory inputs. Neural evidence for multisensory integration (MSI) was seen across all three groups, with the multisensory response differing from the sum of the unisensory responses. Post-hoc tests suggested the possibility of enhanced MSI in SPD in timeframes consistent with cortical sensory registration (~60ms), followed by reduced MSI during a timeframe consistent with object formation (~130ms). The ASD group also showed reduced MSI in the later timeframe. Children with SPD showed reduction in their ability to benefit from redundant audio-visual inputs, similar to children with ASD. Neurophysiological recordings, on the other hand, showed that major indices of MSI were largely intact, although post-hoc testing pointed to periods of potential differential processing. While these exploratory electrophysiological observations point to potential sensory-perceptual differences in multisensory processing in SPD, it remains equally plausible at this stage that later attentional processing differences may yet prove responsible for the multisensory behavioral deficits uncovered here.